2019
DOI: 10.1021/acsmaterialslett.9b00433
|View full text |Cite
|
Sign up to set email alerts
|

Pentacyclic Ladder-Heteraborin Emitters Exhibiting High-Efficiency Blue Thermally Activated Delayed Fluorescence with an Ultrashort Emission Lifetime

Abstract: As one of the three primary colors, blue is significant for display and lighting applications and the development of blueemitting molecules with high quantum efficiency, and color purity for organic light-emitting diodes (OLEDs) remains a key challenge. Herein, a new series of blue thermally activated delayed fluorescence (TADF) materials featuring π-extended ladderoxaborin and thiaborin acceptors has been developed. Steadystate and time-resolved photophysical measurements revealed the advantages of the ladder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 57 publications
(84 reference statements)
0
56
0
Order By: Relevance
“…This requires us to consider the involvement of 3 LE as an intermediate excited state in RISC, which can provide an effective SOC between the 1 CT and 3 LE states with different orbital symmetries necessary for spin flipping in accordance with the El-Sayed rule ( 19 25 ). Very recently, we revealed that in heteraborin-based TADF emitters, the incorporation of a heavier sulfur atom instead of oxygen and nitrogen lead to an intensified SOC between the 1 CT and 3 LE states and, thus, a remarkably high k RISC approaching 10 7 s −1 , which is comparable to k r ( 26 28 ). The introduction of heteroatoms with lone-pair electrons or empty orbitals results in an effective perturbation to the excited-state electronic configurations for accelerating RISC.…”
Section: Resultsmentioning
confidence: 99%
“…This requires us to consider the involvement of 3 LE as an intermediate excited state in RISC, which can provide an effective SOC between the 1 CT and 3 LE states with different orbital symmetries necessary for spin flipping in accordance with the El-Sayed rule ( 19 25 ). Very recently, we revealed that in heteraborin-based TADF emitters, the incorporation of a heavier sulfur atom instead of oxygen and nitrogen lead to an intensified SOC between the 1 CT and 3 LE states and, thus, a remarkably high k RISC approaching 10 7 s −1 , which is comparable to k r ( 26 28 ). The introduction of heteroatoms with lone-pair electrons or empty orbitals results in an effective perturbation to the excited-state electronic configurations for accelerating RISC.…”
Section: Resultsmentioning
confidence: 99%
“…Later, Agou et al (2020) reported the pentacyclic ladderheteraborin blue TADF emitters. Many researchers have investigated the boron-containing π-electron system because of its fascinating properties in terms of TADF emitter.…”
Section: Partially Bridged Boron-type Acceptor For Blue Thermally Actmentioning
confidence: 99%
“…In fact, sky-blue (or green) TADF emitters exhibiting larger kRISCs with one order of magnitude higher than that of HDT-1 have been realized through a strict control of the excited state alignment between a CT state and a LE state. 22 The concept presented here can be applied to other advanced TADF materials to realize more stable pure-blue OLEDs. In addition, we should note that a suppression of direct carrier trapping on a terminal dopant can also improve the operational lifetime.…”
Section: Advanced Hf System With Faster Fret With Less Carrier Trappingmentioning
confidence: 99%